Callous-Unemotional Traits and Cyber Deviance: An Assessment Using Data From College Students in India. - Joo, Sung Hwan; Nedelec, Joseph L. (Crime & Delinquency, 2026)
With growing attention toward cybercrime, researchers have increasingly assessed how individual differences such as personality may impact antisocial behaviors online. In general, research has highlighted that callousness and other traits indicative of reduced empathy increase the likelihood of engaging in cyber deviance. However, much of the existing literature has primarily been based on Western samples. To further probe the influence of personality traits on cyber deviance beyond Western samples, the current study employed self-reported data from university students in India (n = 611). The study evaluated associations between callous-unemotional (C-U) traits and deviant behaviors in cyberspace (unauthorized access, password fraud, and malicious hacking). Overall, the results were mixed, but the findings illustrated that C-U traits appear to be associated with engaging in aspects of cyber deviance. Notably, however, callous-unemotional traits were not associated with malicious hacking in any of the models. The discussion focuses on how the current study adds to the relevant individual personality differences and cyber deviance literature. Suggestions for future research in this burgeoning area are also provided.